2023
DOI: 10.1111/echo.15637
|View full text |Cite
|
Sign up to set email alerts
|

A role for ultra‐high resolution three‐dimensional printed human heart models

Abstract: Introduction Echocardiography is essential for diagnosing and assessing the severity of perioperative structural and functional heart disease. Yet, educational opportunities to better understand echocardiography‐based cardiac anatomy remain limited by the two‐dimensional display, lack of anatomic details, variability of heart models, and costs and global access of training. Methods We performed micro computed tomography of human heart specimens not suitable for orthotopic transplantation. We created high‐resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Regarding the use of 3D-printed heart and vascular models in anatomy education, the most commonly used imaging modalities are CT or MRI for the generation of 3D-printed models. In a recent study, Arango et al reported the feasibility of creating ultra-highresolution 3D-printed heart models using micro-CT [103]. They scanned perfusion-fixed heart specimens using 0.1 mm resolution micro-CT scanning, with the images being postprocessed and segmented for 3D printing.…”
Section: Patient-specific 3d-printed Models: Medical Educationmentioning
confidence: 99%
“…Regarding the use of 3D-printed heart and vascular models in anatomy education, the most commonly used imaging modalities are CT or MRI for the generation of 3D-printed models. In a recent study, Arango et al reported the feasibility of creating ultra-highresolution 3D-printed heart models using micro-CT [103]. They scanned perfusion-fixed heart specimens using 0.1 mm resolution micro-CT scanning, with the images being postprocessed and segmented for 3D printing.…”
Section: Patient-specific 3d-printed Models: Medical Educationmentioning
confidence: 99%